A construção da violência Urbana na Revista Veja - Lisboa, Ingrid Valéria (2007)
This dissertation analysis how the weekly magazine Veja builds the urban violence thematic. Fights, traffic accidents, robberies, thefts and kidnapping are considered acts of urban violence, probably followed by death. Studies were carried out on cover stories that fit in this thematic, some because of the interest on crimes that had big media coverage such as kidnappings and murders, some because it relates urban violence to social-economical themes such as poverty and public security, during the period of 1968 to December 2005. Using the semiotics theory (Denis Bertrand, José Luiz Fiorin, Eric Landowski, Ana Claudia de Oliveira e Diana Luz Pessoa de Barros), research analyzed how Veja builds the theme and the figures of urban violence and criminality; outlined, under the magazine enunciator s perspective, which are the causes and solutions for the urban violence problem (historical and social factors); investigated the communication contracts established between the magazine and its readers; from the narrative point of view, outlined who the subjects and their objects of value are, and how these subjects are modalized; and marked out the passional path of the narrative subjects, what passions move them: their fears, attitudes, threats and believes related to the question of violence